1998
DOI: 10.1002/(sici)1097-0231(19981215)12:23<1899::aid-rcm417>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the enantiomers of salbutamol and its 4‐O‐sulphate metabolites in biological matrices by chiral liquid chromatography tandem mass spectrometry

Abstract: Sensitive, mass spectrometry based bioanalytical methods are described for the determination of the R- and S-enantiomers of the beta-agonist salbutamol (albuterol) and its 4-O-sulphate metabolite in human plasma and urine. In both methods samples are prepared by 96 well format solid phase extraction using a custom built robotic system. Extracts are then analysed by liquid chromatography tandem mass spectrometry (LC-MS/MS) using a teicoplanin-based chiral stationary phase and selected reaction monitoring. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 7 publications
0
32
0
1
Order By: Relevance
“…The plasma levels of d-threo-MPH were substantially higher than those of the l-threo-MPH, which is in accord with previous findings. 1 Recently, Joyce et al 29 reported the determination of salbutamol enantiomers and its 4-O-metabolite using a teicoplanin-based CSP coupled to a triple quadrupole mass spectrometer. Teicoplanin (Chirobiotic T) is also a macrocyclic glycopeptide, which exhibits complementary stereoselectivity to the vancomycin CSP.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma levels of d-threo-MPH were substantially higher than those of the l-threo-MPH, which is in accord with previous findings. 1 Recently, Joyce et al 29 reported the determination of salbutamol enantiomers and its 4-O-metabolite using a teicoplanin-based CSP coupled to a triple quadrupole mass spectrometer. Teicoplanin (Chirobiotic T) is also a macrocyclic glycopeptide, which exhibits complementary stereoselectivity to the vancomycin CSP.…”
Section: Resultsmentioning
confidence: 99%
“…Serum salbutamol concentrations were measured with liquid chromatography-mass spectrometry by Glaxo Wellcome as reported previously. 18 Standard curves were generated using calibration standards at 0.1, 2, 4, 8, 16, 25, and 50 ng/ml salbutamol. For all standard concentrations, the inter-and intra-assay precision (%CV) and the bias were all less than 15% over the limits of quantification.…”
Section: Methodsmentioning
confidence: 99%
“…But the sensitivity of the method with UV detector was not adequate to support bioanalytical studies. The advent of combined LC‐MS has revolutionized bioanalysis providing sensitive and specific methods with fast analysis time . A few LC‐MS/MS methods have been reported for the determination of trantinterol in biological matrices .…”
Section: Introductionmentioning
confidence: 99%